Hubungan Ketersediaan Sumber Daya, Kepemimpinan, Lama Kerja, dan Persepsi dengan Kepatuhan Mencuci Tangan Lima Momen di Rumah Sakit Islam Surabaya - Fahrun Nisa Arsabani; Nevita Putri Nur Hadianti (Jurnal Keperawatan Muhammadiyah, 2019)
Hospital as health care facility has an obligation to make, implement and maintain quality standards for health services. Hospital infection are one of the main causes of death and increased morbidity in patients, which can occur due to non-hygiene behavior, which can be prevented by five moment hand hygiene. However, in Surabaya Islamic Hospital  has a low hand hygiene compliance rate of 81.87% with a target of 85% in the third quarter of 2017.The purpose of this study was to analyze the relationship between the availability of resources, leadership, length of work, and perception with five moment hand hygiene compliance at Surabaya Islamic Hospital. This research was an observational analytic study, by questionnaires and observation to 67 employees of Surabaya Islamic Hospital. The research design was cross sectional with statistical analysis, chi-square.The results showed 56.72% of respondents did not comply with hand hygiene. There were a relationship between the availability of resources (p = 0,032) and perception (p = 0,00) with five moment hand hygiene compliance, while leadership (p = 0,13) and length of work (p = 0,249) were not associated with five moment hand hygiene compliance in Surabaya Islamic Hospital. The conclusion of this study is the condition of five moment hand hygiene compliance in Surabaya Islamic Hospital employees is low with the relationship between the availability of resources and perception with five moment hand hygiene compliance.